THE ECONOMIC VALUE OF GREEN OPEN SPACE AREA IN MEDAN BASED ON TYPE OF LAND USE - Bahruni; Mona Fhitri Srena; Rachmad Hermawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Medan City which is the capital of North Sumatra Province has many environmental problems, so it requires the existence of green open space could ameliorate microclimate. Air temperature and humidity as part of the microclimate element affect the level of comfort that will ultimately affect quality the of society. It is necessary to quantitatively calculate the economic value of the urban forests so that their existence is considered a need for the city. This study aims to estimate the economic value of green open space based on biotic, physical, and social factors in residential areas, business and office areas, and industrial areas in Medan City. The research was conducted in Cadika, Beringin, and Maharani green open spaces. The research data was collected during December 2020-February 2021. The data analysis method is using multiple linear regression analysis. The result showed quantitatively through the green open space temperature humidity index value it falls into the uncomfortable category (THI>26) but qualitatively by perception visitors and communities that urban forests are comfortable. Total WTPs from green open space visitors with a visiting period which is valued at Rp. 29,268,000/year. Based on the hedonic price analysis, the closer 1 meter to the green space will increase the price of different properties in each green open space. Key words: economic value, green open space, Medan City, willingness to pay